Probing the exciton density of states in semiconductor nanocrystals using integrated photoluminiscence spectroscopy - Filonovich, Sergej (2002)
We present the results of a comparative analysis of the absorption and photoluminescence excitation (PLE) spectra vs. integrated photoluminescence (IPL) measured as a function of the excitation wavelength for a number of samples containing II–VI semiconductor nanocrystals (NCs) produced by different techniques. The structure of the absorption and PL spectra due to excitons confined in NCs and difficulties with the correct interpretation of the transmittance and PLE results are discussed. It is shown that, compared to the conventional PLE, the IPL intensity plotted against the excitation wavelength (IPLE spectra) reproduce better the structure of the absorption spectra. Therefore, IPLE spectroscopy can be successfully used for probing the quantized electron-hole (e-h) transitions in semiconductor nanocrystals.